2021
DOI: 10.1002/oby.23125
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Association Between Hypothalamus‐Pituitary‐Adrenal Axis Activity and Obesity: A Meta‐Analysis

Abstract: Objective Both the cortisol awakening response (CAR; corresponding to the state measurement) and hair cortisol concentration (HCC; corresponding to the trait measurement) are considered reliable markers of hypothalamus‐pituitary‐adrenal axis activity. Because cortisol has long been associated with adiposity, this systematic review and meta‐analysis aims to summarize and compare the literature around CAR and HCC and their association with obesity or fat distribution indices. Methods The PubMed, Web of Science (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…While results on the CAR are inconsistent, hair cortisol has been consistently associated with chronic stress, obesity and NCDs, for example cardiovascular disease, recent myocardial infarction, and Diabetes Mellitus (DM) 16,28,8083 . The measure is less prone to methodological errors 16,80 and due to its non-invasive sampling, being independent of the time of day, it may be a reliable indicator in studying the effects of chronic stress on health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While results on the CAR are inconsistent, hair cortisol has been consistently associated with chronic stress, obesity and NCDs, for example cardiovascular disease, recent myocardial infarction, and Diabetes Mellitus (DM) 16,28,8083 . The measure is less prone to methodological errors 16,80 and due to its non-invasive sampling, being independent of the time of day, it may be a reliable indicator in studying the effects of chronic stress on health.…”
Section: Discussionmentioning
confidence: 99%
“…24 Results on the CAR and metabolic diseases are controversial: a blunted CAR has been linked to an unfavourable metabolic and cardiovascular risk profile, 2527 while others found adiposity indices to not be associated with the CAR. 28…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appetite is stimulated by high levels of NPY and CRH, and leptin. Suppression of high cortisol levels during longterm exercise may disrupt this vicious cycle, reducing hunger, improving eating habits, and increasing refusal of highcalorie meals, resulting in weight loss [15]. Stress habituation occurs when repeated exposure to the same stressor (such as prolonged repetitive exercise) occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an association of cortisol and obesity is consistently indicated in the literature. A recent meta-analysis that reviewed studies in humans regarding cortisol awakening response as a state measure for HPA axis activity and hair cortisol as a trait measure found that trait rather than state measures were associated with general and abdominal adiposity in humans ( 102 ). Therefore, HPA axis dysfunction might constitute a critical factor that links obesity and depression.…”
Section: Adipose Tissue Compartments Hypothalamus–pituitary–adrenal A...mentioning
confidence: 99%